"Threatening" mechanism of disorder: evidence from attentional bias. Issue 7 (3rd October 2022) - Zhang, Wenjun; Li, Kaiyun; Yang, Huijing; Xu, YuanYuan; Li, Zhuoyi; Lin, Fengxun
ABSTRACT: The absence of ordered information ("disordered" information) in the environment has various negative influences on individuals: " The world is random " model postulates that disordered information has negative influences through a process of " perceiving disorder leads to threatening feelings ". In experiment 1, attentional bias to disorderly pictures was measured by dotprobe tasks. The results revealed that individuals bias more attention to physical environmental disordered pictures and this process occurs at the strategic processing stage. In experiment 2, the attentional bias of participants to threatening pictures was measured under a disorderliness/orderliness state. The results showed that individuals bias attention to threatening stimuli in the disordered state and this also occurred at the strategic processing stage. In experiment 3, results from Implicit Association Tasks (IATs) showed that individuals implicitly associate disorder and threat concepts. These results empirically demonstrated that disordered information can induce threatening feelings and verified the " The world is random " model.